Совершенствование конструкции молотового штампа - Аралкин, А. С.; Неймирко, С. И. (НТУ "ХПИ", 2013)
Выполнен анализ причин выхода из строя молотовых штампов. Дана оценка времени удара и сил, действующих на штамп при штамповке. Расчетным путем установлены температурные деформации деталей в месте установки центрирующей шпильки. Получены параметры деформации в месте сопряжения шпильки и штампа. Разработаны конструктивные мероприятия, повышаю щие надежность работы центрирующих шпилек и штампа в целом

The analysis of reasons of death hammer of stamps is executed. The estimation of time of blow and forces, operating on a stamp at stamping, is Given. A calculation path is set temperature deformations of details in the place of setting of centering hairpin. The parameters of deformation are got in the place of interface of hairpin and stamp. Structural measures are worked out, a step -up reliability of work of centering hairpins and stamp on the whole
Keywords: центрирующие шпильки; сила удара; температурные деформации; упругие перемещения; энергия деформации; потери энергии; штамповка; hammer stamp; construction; centering hairpins; power of a blow; temperature deformations; resilient moving; energy of deformation; loss of energy